Pengaruh Penerapan Good Governance, Temuan Audit dan Indikasi Korupsi terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten/Kota di Provinsi Sumatera Barat - Muhammad Fajar Alhamdi; Fefri Indra Arza; Ridha Azka Raga (Universitas Negeri Padang, 2026)
Local governments in West Sumatra Province will have their financial performance monitored from 2020 to 2024. The impact of good governance practices, audit findings, and corruption signs will be examined. The research uses a quantitative method, assessing data from 19 regencies/cities, and is motivated by repeated issues of budget mismanagement and insufficient oversight in places including Dharmasraya, Mentawai, and Padang. Sources of secondary data included government documents such as LKPD records, BPK audit reports, and KPK files. The audit results were collected from BPK evaluations, the Procurement Governance Index (ITKP) was used to measure good governance, and dummy variables derived from court orders were used to categorize corruption signals. Efficiency ratios were used to evaluate financial success. Financial performance is positively affected by good governance, according to the data, but audit findings and corruption indications have a negative effect. These results highlight the importance of effective anti-corruption enforcement, audit integrity, and high-quality governance in enhancing the financial results of the public sector. Enhancing fiscal accountability at the regional government level is the practical goal of this research, which also adds to the growing body of knowledge in public sector accounting.